The Use of Active Learning Strategies to Foster Effective Teaching in Higher Education Institutions - Aryan Hussein Sulaiman Dzaiy; Saman Ahmed Abdullah (Zanco Journal of Humanity Sciences)
Active learning techniques are increasingly being adopted in higher education to foster student engagement and improve learning outcomes. This paper critically examines active learning strategies and their impacts on undergraduate teaching effectiveness. A comprehensive review of the literature provides defines a precise definition of active learning and succinctly summarizes key techniques, including like collaborative exercises, problem-based learning, discussions, simulations, and games. The theoretical basis foundation highlights constructivist and social learning principles. Empirical studies showcased in the literature demonstrate that active learning improves academic achievement, conceptual understanding, critical thinking, motivation, and inclusiveness compared to traditional passive lecture formatss. Practical implementation recommendations focus on the gradual integration of active learning, alignment to with specific learning objectives, scaffolding of student participation, and the incorporation of continuous assessment. Despite challenges of related to student resistance, instructor skills, and resource constraintss, the evidence underscores the active learning's essential role in of active learning in delivering high-quality undergraduate education given it demonstrated cognitive and non-cognitive benefits for diverse learners.